Expectations in culturally unfamiliar music: influences of proximal and distal cues and timbral characteristics - Stevens, Catherine J.; Tardieu, Julien; Dunbar-Hall, Peter; Best, Catherine T.; Tillmann, Barbara (Frontiers in Psychology, 2013)
Listeners’ musical perception is influenced by cues that can be stored in short-term memory (e.g. within the same musical piece) or long-term memory (e.g. based on one’s own musical culture). The present study tested how these cues (referred to as respectively proximal and distal cues) influence the perception of music from an unfamiliar culture. Western listeners who were naïve to Gamelan music judged completeness and coherence for newly constructed melodies in the Balinese gamelan tradition. In these melodies, we manipulated the final tone with three possibilities: the original gong tone, an in-scale tone replacement or an out-of-scale tone replacement. We also manipulated the musical timbre employed in Gamelan pieces. We hypothesized that novice listeners are sensitive to out-of-scale changes, but not in-scale changes, and that this might be influenced by the more unfamiliar timbre created by Gamelan “sister” instruments whose harmonics beat with the harmonics of the other instrument, creating a timbrally shimmering sound. The results showed: 1) out-of-scale endings were judged less complete than original gong and in-scale endings; 2) for melodies played with “sister” instruments, in-scale endings were judged as less complete than original endings. Furthermore, melodies using the original scale tones were judged more coherent than melodies containing few or multiple tone replacements; melodies played on single instruments were judged more coherent than the same melodies played on sister instruments. Additionally, there is some indication of within-session statistical learning, with expectations for the initially-novel materials developing during the course of the experiment. The data suggest the influence of both distal cues (e.g. previously unfamiliar timbres) and proximal cues (within the same sequence and over the experimental session) on the perception of melodies from other cultural systems based on unfamiliar tunings and scale systems.